2012
DOI: 10.1016/j.visres.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The development of speed discrimination abilities

Abstract: The processing of speed is a critical part of a child's visual development, allowing children to track and interact with moving objects. Despite such importance, no study has investigated the developmental trajectory of speed discrimination abilities or precisely when these abilities become adult-like. Here, we measured speed discrimination thresholds in 5-, 7-, 9-, 11-year-olds and adults using random dot stimuli with two different reference speeds (slow: 1.5 deg/s; fast: 6 deg/s). Sensitivity for both refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 51 publications
7
55
0
Order By: Relevance
“…Our findings agree with the view of Ellemberg and colleagues (Ellemberg et al 2004), who observed larger immaturity for slower velocities (1.5 deg/s) than for faster velocities (6 or 9 deg/s). Several authors also showed that dorsal stream vulnerability affects global motion perception in subjects with developmental disorders, as well as weak readers in typical stages of development (Braddick, Atkinson, and Wattam-Bell 2003;Manning, Agten-Murphy, and Pellicano 2012;Milne et al 2002;Pellicano et al 2005;Chen et al 2003;Palomares and Shannon 2013;Cornelissen et al 1998b). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings agree with the view of Ellemberg and colleagues (Ellemberg et al 2004), who observed larger immaturity for slower velocities (1.5 deg/s) than for faster velocities (6 or 9 deg/s). Several authors also showed that dorsal stream vulnerability affects global motion perception in subjects with developmental disorders, as well as weak readers in typical stages of development (Braddick, Atkinson, and Wattam-Bell 2003;Manning, Agten-Murphy, and Pellicano 2012;Milne et al 2002;Pellicano et al 2005;Chen et al 2003;Palomares and Shannon 2013;Cornelissen et al 1998b). …”
Section: Discussionmentioning
confidence: 99%
“…Other authors (Parrish et al 2005;Hayward et al 2011) demonstrated that developmental trajectories of visual motion processing exhibit saturation after 6-7 years of age. It is widely accepted that inherent limits to the integration of neuronal responses in motion sensitive areas can influence the late development of velocity processing abilities in early childhood (Manning, Agten-Murphy, and Pellicano 2012). Laycock and colleagues (Laycock et al 2006) found that a manifestation of this phenomenon in the magno-dominated dorsal stream-especially area MT/V5-is responsible for motion sensitivity and the functional integrity of motion perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to exhibiting tactile, somatosensory, and auditory sensitivities, individuals with ASD often show abnormalities in visual integration and global motion processing [3336]. Based on these and similar findings, a “dorsal stream vulnerability” hypothesis has been proposed, wherein the late-maturing neural systems that underlie motion perception (dorsal stream) are more susceptible to early genetic or environmental effects than earlier maturing neural systems that underlie form perception (ventral stream) [3739]. The finding that a lack of Cntnap2 results in decreased visually evoked activity specifically in dorsal stream-associated visual areas in response to moving gratings is in line with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%